Endovascular Treatment of Large or Giant Non-saccular Vertebrobasilar Aneurysms: Pipeline Embolization Devices Versus Conventional Stents - Jiejun Wang; Luqiong Jia; Zhibin Duan; Zhongxiao Wang; Xinjian Yang; Yisen Zhang; Ming Lv (Frontiers in Neuroscience, 2019)
BackgroundEndovascular treatment of large or giant non-saccular vertebrobasilar aneurysms (VBAs) by conventional stents is difficult and has unsatisfactory outcomes.ObjectThis study was performed to retrospectively analyze the safety and efficacy of a flow diverter in treating large and giant non-saccular VBAs.MethodsWe identified 78 patients with 83 large or giant non-saccular VBAs who accepted endovascular treatment with a pipeline embolization device (PED) or conventional stent from January 2014 to June 2018. The technical details of the procedure, procedure-associated complications, angiographic outcomes, and clinical outcomes were evaluated.ResultsForty-two patients (53.8%, 42/78) with 44 aneurysms (53.0%, 44/83) underwent endovascular treatment with PEDs. Thirty-six patients (46.2%, 36/78) with 39 aneurysms (47.0%, 39/83) underwent endovascular treatment with conventional stents. The complication rate of PED group and conventional stent group was 7.1% (3/42) and 5.6% (2/36), respectively (odds ratio, 0.765; 95% confidence interval, 0.121–4.851; P = 0.776). During a median follow-up time of 28.8 months, the complete occlusion rate in the PED group and conventional stent group was 90.2% (37/41) and 70.3% (26/37), respectively (odds ratio, 3.913; 95% confidence interval, 1.122–13.652; P = 0.032).ConclusionEndovascular treatment with a PED is a promising and safe modality for large and giant non-saccular VBAs, and the complication rate is acceptable, compared with conventional endovascular treatment.